Development of Mathematics e-Modules based on PjBL STEM on Materials Constructing Flat Side Spaces to Improve Mathematical Communication Ability of Junior High School Students - Seftiana Wandani; Reza Kusuma Setyansah; Titin Masfingatin (STAI Hubbulwathan Duri, 2023)
This development research aims: 1) To find out the validity, practicality, and effectiveness of the PjBL STEM-based Mathematics e-Module on the material of Constructing Flat Side Spaces. 2) Knowing the increase in mathematical communication skills of class VIII B students of SMPN 2 Sawahan after using the PjBL STEM-based Mathematics e-Module. The development model in this research uses 4D which consists of Define, Design, Development, and Dissemination. The instruments used include a learning device validation sheet to determine the validity of the developed e-module, student response questionnaires to determine the practicality of the developed e-module, and learning outcomes tests to determine the effectiveness of the developed e-module. The results showed: 1) the PjBL STEM-based Mathematics e-Module on the Flat Sided Space Building material met the validity criteria, the average validation sheet obtained a value of 94% with the